2022
DOI: 10.3389/fpubh.2022.921980
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with access to healthcare services for older adults with limited activities of daily living

Abstract: BackgroundLimited studies focused on the situation and related factors of access to healthcare services for older adults with limited activities of daily living (ADL) in China. This study explores factors associated with access to healthcare services of them based on Andersen's healthcare utilization model (namely, need, predisposing, and enabling dimensions).MethodsA total of 3,980 participants aged 65 years and older adults with limited ADL from the latest wave (2018) of the Chinese Longitudinal Healthy Long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…Nevertheless, this research failed to find a significant relationship between per-capita household expenditure quintiles and the probability of inpatient service use, which consolidates a prior study in China [ 5 ]. Overall, consistent with prior research in China [ 5 , 45 ], our finding may indicate great disparities in whether to access outpatient services and the number of inpatient service use among different socioeconomic groups of people aged over 45 years who require regular health care. As patient’s willingness to access health services mainly depends on reimbursement rates of health insurance plans [ 5 , 13 ], further optimizing health insurance schemes is needed, particularly for outpatient services [ 5 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nevertheless, this research failed to find a significant relationship between per-capita household expenditure quintiles and the probability of inpatient service use, which consolidates a prior study in China [ 5 ]. Overall, consistent with prior research in China [ 5 , 45 ], our finding may indicate great disparities in whether to access outpatient services and the number of inpatient service use among different socioeconomic groups of people aged over 45 years who require regular health care. As patient’s willingness to access health services mainly depends on reimbursement rates of health insurance plans [ 5 , 13 ], further optimizing health insurance schemes is needed, particularly for outpatient services [ 5 ].…”
Section: Discussionsupporting
confidence: 90%
“…Per-capita household expenditure is a better proxy for financial capacity in the context of China [ 3 , 11 , 52 , 53 ], but has less likely been used in the literature. Also, the relationship between SES and health service use is conflicting–some studies show a positive relationship [ 5 , 8 , 23 , 26 , 45 , 47 , 48 , 51 ], whereas others reveal no association [ 5 , 6 , 19 , 52 ]. Moreover, little is known about whether the impact of SES on health service use differs across morbidity status (i.e., no NCDs, a single NCD, and multimorbidity) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors related to the accessibility of health care services were comprehensive and complex, and previous research has found that the relevant factors included the uneven distribution of resources, inconvenience in mobility, economic burden and lack of help from informal caregivers (53)(54)(55)(56). Mai (57) argued that policies such as full health care insurance coverage, telemedicine and the family doctor system (to a great extent) could realize geographic and service accessibility. However, help from informal caregivers always plays an important role in this scenario.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of matching supply and demand, the demand for health care in old age is analyzed ( 23 ). In terms of countermeasure research, intervention strategies are provided from the perspectives of medical care integration, matching supply and demand, legislative optimization, and equalization of elderly care services, technological tools, Internet of Things devices, life intervention mechanisms, and medical diagnosis ( 24 30 ). In terms of spatial analysis, scholars have conducted analyses at different spatial scales, which are divided into four main categories: first, spatial-temporal analysis at the national scale.…”
Section: Introductionmentioning
confidence: 99%